A Cambrian age for the upper Bambuí Group, Brazil, supported by the first U-Pb dating of volcaniclastic bed. (April 2020) - Moreira, Débora Silvano; Uhlein, Alexandre; Dussin, Ivo Antônio; Uhlein, Gabriel Jubé; Pimentel Misuzaki, Ana Maria
Abstract: The Serra da Saudade Formation is part of the Bambuí Group, a cratonic cover from the western São Francisco craton. It is composed by siliciclastic sediments deposited in a foreland basin during a transgressive event. The Serra da Saudade Formation is mainly represented by rhythmites, siltstones (locally glauconitic) and rare sandstones. The glauconitic siltstone was deposited during a maximum flooding surface and sediment starvation, which allowed high concentrations of probable volcanic-sourced potassium. The interpretation of the depositional age of the Bambui Group had multiple turnovers in the last decades. Finding and dating synsedimentary volcanic rocks is essential to solve this conundrum. This paper presents the first U-Pb direct dating of the Bambuí Group from zircon grains recovered from a volcaniclastic layer interbedded with glauconitic siltstones from the upper Serra da Saudade Formation. A total of 107 U-Pb ages were obtained by LA-ICP-MS and plotted into a Concordia diagram. The provenance signature comprises a wide range of detrital zircon ages (1.0–2.8 Ga). These data represent inherited zircon grains incorporated into the magma during magmatic activity that produced the volcanic sediment, or to dilution and reworking of volcanic ashes that mixed to fine-grained clastic sediments prior to deposition. A significant amount of 10 highly concordant, prismatic zircon grains clustered into a well constrained age of 520.2 ± 5.3 Ma, which represent the explosive volcanic eruption age, and by extent, the depositional age of the upper Serra da Saudade Formation. Since the currently final thrust stacking ages from the Brasilia Belt and the Araçuaí Belt are dated ca. 600 and 540 Ma, respectively, one must carefully look for the real age of the deformation event that affected the Bambuí Group over the São Francisco craton. Graphical abstract: Image 1 Highlights: Stratigraphy, petrography and geochronology of Serra da Saudade Formation, Bambuí Group. The glauconitic siltstone was deposited in a foreland basin during low sedimentation rates and related to volcanic processes. The volcanoclastic layer described in the upper Bambuí Group reveals a sedimentation age of 520.2 ± 5.3 Ma. The Bambuí Group spanned the Ediacaran-Cambrian boundary and was deformed during the Cambrian Period.